(untitled) (Hombre, Ciencia y Tecnología, 2018)
The environment is a constant concern in the country since last century. Climate deterioration, the erosion of fertile soils and other issues have forced to design strategies to cope with Guantánamo’s environmental deterioration, which has constituted a theme of investigation for professionals dedicated to the study of Nature and the society. The insufficient economical analysis aimed at the environmental management is a necessary element for the destination of financial resources. It is required to implement control actions that make possible a rational distribution of the intended incomes to the environmental management, training to the professionals in order to widen their knowledge on the Tax System, stimulate the use of the Environment Fund as an economical instrument, apply theoretical methodological experiences existing in the territory to encourage and consolidate the construction of a socialist and sustainable society in terms of economy for the local development.